Relationship between Anthropometric indices, serum Leptin and Respiratory function in Myanmar male adult subjects - Zaw, Thurein; Hlaing, Zarchi Theint-Theint; Sein, Mya Thanda (Asian Journal of Medical Sciences, 2019)
Background: The role of leptin in respiratory function has been studied in specific respiratory disease. A little is known about the association of serum leptin level and respiratory function parameter in healthy subjects. Aims and Objectives: This study aimed to investigate the relationship between anthropometric indices, serum leptin and respiratory function in Myanmar male adult subjects Material and Methods: A community- based cross-sectional comparative study was carried out in 101 apparently healthy male adult subjects of age 18-45 years. All participants were categorized by anthropometric indices into non- obese (body mass index: BMI < 25 Kg/m2 and obese subjects (BMI > 30 Kg/m2). Differences in respiratory function parameter and serum leptin level were compared across the group. Spirobank II spirometer was used to measure respiratory function (FEV1, FVC, FEV1/FVC, PEFR and FEF25-75%). Serum leptin level was investigated by enzyme-linked immunosorbent assay. Results: The percentage of predicted value of all respiratory function parameters of obese group was significantly lower than that of non-obese group (p <0.05). All respiratory function parameters were significantly and negatively correlated with body mass index (BMI) and waist circumference (WC). Median and interquartile range of serum leptin level in the obese group was 5.8(3.5-9.1) ng/mL and it was significantly higher than that of non-obese group [1.9(1.1-3.1) ng/mL, p <0.001]. Serum leptin level was significantly and negatively correlated with respiratory function parameters (FVC, FEV1/FVC, PEF and FEF25-75%). Conclusion: Respiratory function declined with increasing anthropometric indices might be due to increased serum leptin level considered as systemic inflammatory effect of body.